Analisis Beban Kerja Mental Dosen Fakultas XYZ Menggunakan Metode Nasa TLX - Dewi, Grita Supriyanto; Finansia, Cici; Lahitani, Alfirna Rizqi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Employee performance is influenced by several things, one of which is work stress. Unresolved stress results in a person's inability to interact positively with their environment. XYZ Faculty is one of the faculties in a private university in the Yogyakarta area. Based on personnel data, the average 2023 BKD for XYZ Faculty lecturers is 18.65. This creates an excessive burden on lecturers. This research aims to measure the mental workload index of XYZ faculty lecturers and develop recommendations for improvement to balance the workload. The method used in this research is the Nasa TLX method. The results of the research show that the workload experienced by lecturers at Faculty so that administrative activities do not interfere with lecturers' tri dharma activities.